Mechanical Design of a Hybrid Leg Exoskeleton to Augment Load-Carrying for Walking. (27th November 2013) - Miao, Yunjie; Gao, Feng; Pan, Dalei
An innovative lower extremity exoskeleton, SJTU-EX, is demonstrated in Shanghai JiaoTong University, which mainly aims to help soldiers and workers to support a payload in motion. This paper summarizes the mechanical design of SJTU-EX. Each pseudo-anthropomorphic leg of SJTU-EX has four active joints and two passive joints, and the joint ranges are optimized in consideration of both safety factors and the realization of typical motions. Springs are applied in the leg to eliminate the effect of gravity. The results of dynamic simulations are used to determine the actuated joints and the passive joints. Novel Hy-Mo actuators are introduced for SJTU-EX and the layout of the actuator for Diamond Side 2 is described in detail as a design example.